Implementation of an Iot System in The Teaching Factory: Optimization of The Salted Fish Drying Process - Fitrinaldi, Fitrinaldi (Syntax Corporation, 2024)
Drying is a preservation method commonly used in the food industry to extend the shelf life of food by reducing the water content to a safe level. However, traditional drying methods, such as sun drying, are highly dependent on weather conditions and often produce inconsistent product quality. This research aims to optimize the salted fish drying process through the application of the Internet of Things (IoT) in the Teaching Factory environment, with a focus on monitoring and controlling temperature and humidity in real-time. The test results show that the temperature on sensor 1 reached 43.8°C, sensor 2 was 41.1°C, and sensor 3 was 49.6°C, with average humidity ranging from 35.6% to 57.8%. Drying time varies between 8-12 hours, depending on the type of biota being dried. These tests revealed that water vapor could be removed efficiently without being trapped, ensuring optimal drying. In addition, the application of IoT in the Teaching Factory provides educational value for students with relevant industry skills. This innovation offers a solution to traditional drying challenges, such as variations in product quality and the risk of microbial contamination. Therefore, the integration of IoT in the salted fish drying process has the potential to improve production standards and competitiveness in the global market.